Anti-Inflammatory Activity of Lactobacillus on Carrageenan-Induced Paw Edema in Male Wistar Rats - Sarika Amdekar; Purabi Roy; Vinod Singh; Avnish Kumar; Rambir Singh; Poonam Sharma (Hindawi Limited, 2012)
Introduction. Lactobacillus casei and Lactobacillus acidophilus were used to assess the anti-inflammatory properties in carrageenan induced acute inflammatory model. Materials and Methods. Diclofenac sodium was used as standard drug at concentration of 150 mg/kg of body weight. Culture of Lactobacillus  2×107 CFU/ml was given orally. Edema was induced with 1% carrageenan to all the groups after one hour of the oral treatments. Paw thickness was checked at 𝑡=1, 2, 3, 4, 5, and 24 hours. Stair climbing score and motility score were assessed at 𝑡=24 hours. Cytokines assay for IL-6, IL-10, and TNF-α was performed on serum samples. Results. Lactobacillus showed a statistically significant decrease in paw thickness at 𝑃<0.001. L. acidophilus and L. casei decreased by 32% and 28% in paw thickness. They both significantly increased the stair climbing and motility score. Lactobacillus treatment significantly downregulated IL-6 and TNF-α while upregulated IL-10 at 𝑃<0.0001. Conclusion. L. casei and L. acidophilus significantly decreased the inflammatory reactions induced by carrageenan. This study has also proposed that Lactobacillus ameliorated the inflammatory reaction by downregulating the proinflammatory cytokines pathway.